Case Report: FGFR1 mutation and massive chromosome loss drive malignant transformation of low-grade gliomas - Tang, Ruze; Chen, Yanming; Wan, Dong; Xiang, Yongjun; Chen, Si; Chen, Huafei; Dai, Xiaoxiao; Rong, Rong; Xiao, Sheng; Lan, Qing; Wang, Hangzhou; Huang, Shungen (Frontiers in Oncology, 2025)
The mitogen-activated protein kinase (MAPK) signaling pathway plays roles in cell proliferation, differentiation, and apoptosis, all crucial for cellular transformation. It’s no surprise that MAPK alterations are prevalent in numerous tumors. Several critical genes in the MAPK signaling pathway, including BRAF, FGFR, and NF1, are mutated in brain tumors. For example, FGFR1 mutation or rearrangement has been described in pilocytic astrocytoma, diffuse astrocytoma, and dysembryoplastic neuroepithelial tumor (DNT). These MAPK-activated brain tumors are benign and seldom progress to malignancies, with the mechanisms driving this rare transformation not yet fully understood. In this study, we present two cases of high-grade glioma characterized by a single activating mutation of FGFR1 and massive chromosome loss (near-haploid genome). Similar haploidy is found in 3 additional high-grade astrocytoma by literature review, all harbor a single gene mutation in the MAPK pathway. We propose that the massive chromosome loss might serve as a significant mechanism contributing to the unusual malignant transformation of benign brain tumors activated by the MAPK pathway.